2018
DOI: 10.1002/cbdv.201800219
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Anti‐Diabetic Activity of Polysaccharide from Cordyceps cicadae in Experimental Diabetic Rats

Abstract: Cordyceps cicadae is a medicinal fungus used in treating night sweat, childhood convulsions, vision improvement and pain. This study was designed to evaluate the anti-diabetic activity of the crude polysaccharide (SHF) from the mycelium and body portion of C. cicadae. Diabetes mellitus was induced in the rat with a single intravenous injection of alloxan monohydrate (150 mg/kg). In other to evaluate the anti-diabetic effects of C. cicadae polysaccharide in alloxan-induced diabetic rats, the crude polysaccharid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…The insulin sensitivity index was increased, the levels of fasting blood glucose and fasting insulin were reduced, and the number of apoptotic cells and the expressions of both homologous protein and c-Jun were decreased in the diabetic rats. Cordyceps cicadae crude polysaccharides decreased blood glucose of diabetic rats, total cholesterols, triglycerides, low-density lipoprotein, malondialdehyde, urea, creatinine, alanine transaminase, aspartate aminotransferase and alkaline phosphate, and increased body weight, high-density lipoprotein, SOD and GPx [ 137 ]. According to Tang et al [ 138 ], six fractions of polysaccharides derived from different parts (whole plants, roots and leaves) of Anoectochilus roxburghii and Anoectochilus formosanus were fed to streptozocin-induced diabetic mice and the body weight, blood glucose, glycogen, insulin, total cholesterols, triglycerides, low-density lipoprotein, high-density lipoprotein, malondiadehyde, and antioxidant enzyme activities in the liver and kidney of mice were tested.…”
Section: Polysaccharides and Healthmentioning
confidence: 99%
“…The insulin sensitivity index was increased, the levels of fasting blood glucose and fasting insulin were reduced, and the number of apoptotic cells and the expressions of both homologous protein and c-Jun were decreased in the diabetic rats. Cordyceps cicadae crude polysaccharides decreased blood glucose of diabetic rats, total cholesterols, triglycerides, low-density lipoprotein, malondialdehyde, urea, creatinine, alanine transaminase, aspartate aminotransferase and alkaline phosphate, and increased body weight, high-density lipoprotein, SOD and GPx [ 137 ]. According to Tang et al [ 138 ], six fractions of polysaccharides derived from different parts (whole plants, roots and leaves) of Anoectochilus roxburghii and Anoectochilus formosanus were fed to streptozocin-induced diabetic mice and the body weight, blood glucose, glycogen, insulin, total cholesterols, triglycerides, low-density lipoprotein, high-density lipoprotein, malondiadehyde, and antioxidant enzyme activities in the liver and kidney of mice were tested.…”
Section: Polysaccharides and Healthmentioning
confidence: 99%
“…In recent years, the hypoglycemic and/or hypolipidemic effects of polysaccharides derived from Cordyceps species has been frequently investigated. For example, Zhang et al [10] investigated the anti-hyperglycemic, anti-hyperlipidemic, and antioxidant activities of C. cicadae polysaccharide in alloxan-induced diabetic rats. Li et al [11] found that C. sinensis polysaccharide decreased serum blood glucose levels and increased serum insulin levels in STZ-induced diabetic rats and alloxan-induced diabetic mice; C. militaris polysaccharide displayed a more prominent hypoglycemic effect than that of C. sinensis polysaccharide [12].…”
Section: Discussionmentioning
confidence: 99%
“…Cordyceps , a traditional Chinese medicinal macrofungus, is recognized as a valuable source in the search for natural active polysaccharides and has been used for thousands of years as medicine and food. Previous studies have found that polysaccharides from Cordyceps cicadae , Cordyceps sinensis , or Cordyceps militaris exerted potent anti-diabetes effects [1012]. Cordyceps taii is native to southern China and was first discovered, identified, and named by Professor Zongqi Liang in Guizhou Province in 1991.…”
Section: Introductionmentioning
confidence: 99%
“…The main components of CE are detected and include exopolysaccharide, amino acid, and adenosine. Polysaccharides are reported to be effective as a moisturizer and have been shown in clinical trials to treat diabetes . Studies have shown that amino acids can promote cell proliferation and play an important role in maintaining intestinal health .…”
Section: Discussionmentioning
confidence: 99%